1995
DOI: 10.1093/ajcn/61.2.410s
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, tooth development, and dental caries

Abstract: Many studies involving small animals have clearly shown that malnutrition affects tooth formation and causes increased dental caries. We have conducted two cross-sectional studies and one longitudinal study among Peruvian children to investigate the effect of early malnutrition on oral health. The cross-sectional studies have shown that in malnourished children the pattern of caries development as a function of age is significantly altered as a result of a delayed eruption and exfoliation of the deciduous teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
14

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 15 publications
2
95
0
14
Order By: Relevance
“…The use of peak caries activity has allowed the observation of a strong association between malnutrition and increased dental caries (Alvarez, 1995). It was found that chronic malnutrition vis a vis under nutrition reduced the secretion rate of stimulated saliva, but not that of unstimulated saliva.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of peak caries activity has allowed the observation of a strong association between malnutrition and increased dental caries (Alvarez, 1995). It was found that chronic malnutrition vis a vis under nutrition reduced the secretion rate of stimulated saliva, but not that of unstimulated saliva.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, poor nutrition affects tooth eruption and outcome demonstrated delayed emergence of the deciduous teeth. There appears to be a physiological association between skeletal growth and tooth eruption (Barrett & Brown, 1966;Mukherjee, 1973;RamiReddy et al, 1986;Banerjee et al, 1992;Alvarez, 1995;Chiu et al, 2012). A change in the pattern of tooth eruption should result in a concomitant change in the age distribution of dental caries in the primary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation was observed between the degree of linear enamel hypoplasia and caries experience in the deciduous teeth of undernourished Guatemalan children 9 . Notably, malnutrition (wasting or stunting)…”
mentioning
confidence: 89%
“…Infante 21 ; verificaram que a desnutrição retarda a cronologia de erupção dentária, o que implica dizer que crianças desnutridas têm seus dentes expostos ao meio bucal mais tardiamente. Segundo Alvarez 22 , este atraso de erupção alteraria o padrão de desenvolvimento da cárie dentária, uma vez que a colonização da cavidade oral por Estreptococos do Grupo Mutans (EGM) ocorre após a erupção do primeiro dente. Isto porque se faz necessária a presença de uma superfície que permita a organização de um biofilme cariogênico 23 .…”
Section: E R U P ç ã O D E N T á R I Aunclassified
“…O estudo de 209 crianças peruanas confirmou que existe uma relação de causa e efeito entre desnutrição precoce e aumento de cárie dentária 20 . Em 1995, Alvarez 22 relatou que um único episódio de desnutrição leve ou moderada no primeiro ano de vida possui a capacidade de aumentar a manifestação da cárie dentária tanto na dentição decídua, como anos depois na dentição permanente.…”
Section: á R I E D E N T á R I Aunclassified